Sollen Das and Sein Legal Protection for Child Victims of Criminal Acts of Domestic Violence From a Victimological Perspective - Mamay Komariah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Growth and development as well as the fulfillment of all necessities of life are absolutely necessary for a child who is the next generation. In fact, it is not uncommon for a crime or crime to be committed against children. In fact, in some cases where there are criminal acts of violence both physically and psychologically, it is carried out by the closest environment in the child's life, namely his own family. This study discusses the causes of a child becoming a victim of violence in the family by using victimology in its approach. This is necessary so that in the future the state within the existing legal system can protect the rights of children who are victims of criminal acts of physical and psychological violence in their family. This type of legal research is a type of normative legal research, which aims to review the provisions of positive law in this case criminal law as a source of law. The problem approach in legal research uses the statutory approach, carried out by reviewing existing laws and regulations relating to the legal issues being discussed. In this discussion provides conclusions and suggestions that uniformity is needed regarding the regulation of legislation regarding the age limits of a person can be qualified as children, so as not to cause confusion and difficulties in its implementation.